Exploring Drawing Art to Develop Creativity in Early Childhood at PAUD Riyadul Arshaka - Putri, Chika Amelia (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2025)
Developing creativity through art, including drawing, is a crucial element in PAUD. Field research methods were used, with data collection through observation, interviews and documentation at PAUD Riyadul Arshaka. The results of the research show that the practice of drawing in PAUD contributes to children's artistic and cognitive development. Children show high enthusiasm in expressing ideas and feelings through drawings, especially when given freedom of expression. The role of teachers, especially in providing supportive guidance, is very influential in developing children's creativity. Differences in preferences between boys and girls are also visible, highlighting the need for inclusive educational approaches that support the development of creativity according to the uniqueness of individual children.